Role of Molecular Biology in Cancer Treatment: A Review Article - Aman IMRAN; Hafiza Yasara QAMAR; Qurban ALI; Hafsa NAEEM; Mariam RIAZ; Saima AMIN; Naila KANWAL; Fawad ALI; Muhammad Farooq SABAR; Idrees Ahmad NASIR (Iranian Journal of Public Health, 2017)
Background: Cancer is a genetic disease and mainly arises due to a number of reasons include activation of oncogenes, malfunction of tumor suppressor genes or mutagenesis due to external factors.